EFEKTIFITAS PEMBERIAN UPAH LEMBUR TERHADAP KARYAWAN DI SALON SOFI MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Emilia; Iwan Riswandie; Adwin Tista (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
Overtime pay is a form of legal protection for workers who work beyond normal working hours. Law Number 13 of 2003 Article 78 stipulates that workers who perform overtime work are entitled to compensation in the form of overtime pay. However, in practice, the implementation of this regulation is often not optimal, especially in the small business sector such as beauty salons. Sofi Salon in Banjarmasin City was the object of research because it often implements an overtime work system, especially on weekends. Based on observations and interviews, it was found that employees work overtime almost every day, but do not receive overtime pay in accordance with legal provisions. This raises questions about the effectiveness of the implementation of overtime pay at that place and its impact on employee rights and work motivation.